Prospects of GSM technology for academic libraries services (2005)
Purpose- Poor telecommunication infrastructure has been generally identified as a hindrance to most library activities in Nigeria. However, with the emergence and spread of wireless technologies, especially the global system of mobile communications (GSM), this paper seeks to consider the implications of this event on library services, with suggestions on the possible applications to academic libraries. Design/methodology/approach- A background study of information and communication technology staus past and present in Nigeria was carried out, especially the impact of wireless technologies on the global scale and the country. Findings- The GSM technologies acceptance and growth rate among the Nigerian populace has serious and great potentials for enhancing the communication and information technology- related services in libraries and information centres in Nigeria. However, information managers need to fully exploit the opportunities presented by this relatively new phenomenon with a view to providing improved products and services to the library users, especially in the academic sector. Originality/value- This paper highlights the use of GSM technologies library services. It targets librarians and information managers who have been limited in the past by inadequate telephone/telecommunications infrastructure. Encourages the professionals to exploit the oppurtunities presented by these expanding technologies.